THE STUDY OF ARCHAEOASTRONOMY: THE ALIGNMENT TO THE CELESTIAL OBJECTS OF THE TEMPLES IN CENTRAL JAVA - AINI (NIM: 10314001), NURUL
Archeoastronomy is a science that studies the ancient human knowledge about celestial objects through the relics of artifacts, buildings, and culture. One of the archaeoastronomy practices is to explain alignment building with the position of celestial bodies. Some studies have proved that temples in central Java, such as Prambanan, Borobudur, Kalasan, Sewu, and Pawon temples have the alignment with objects in the sky (Sun and/or Moon). The author also looks for the alignments of temples in Central Java by counting the declination from the direction of the temple. From the calculation of temple declination on horizon height values for celestial objects at rising and/or setting, 12 of the 32 temple declinations in Central Java have alignment with the equinox, winter solstice and zenith passage of the Sun. In addition, the possibility of alignment searching with calculations declination direction facing the temple at various heights (0o-90o). Based on these results, 6 of the 20 temples in Central Java at an altitude of nearly zenith passage have an alignment with the Sun.